2004
DOI: 10.1590/s0034-72992004000100014
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação da influência da idade no potencial evocado auditivo de tronco encefálico

Abstract: O potencial evocado auditivo de tronco encefálico (ABR) é um método simples, objetivo e não invasivo de avaliação das vias auditivas do tronco encefálico, que pode ser realizado em qualquer idade e que detecta a atividade elétrica desde a orelha interna até o colículo inferior. O ABR é composto por 7 ondas (I -VII), sendo as ondas I, III e V os componentes mais importantes. O nível de sensação (NS) é uma unidade de estí-mulo que se baseia no limiar psicoacústico do indivíduo e a esse limiar acrescenta-se uma d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
18
0
9

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 16 publications
4
18
0
9
Order By: Relevance
“…The latency and interval values observed in this study are in agreement with those obtained in dogs by other authors (Marshall, 1985;Knowles et al, 1988;Haagen et al, 1989;Harcourt et al, 2010) but shorter than those reported in human studies (Anias et al, 2004;Bento et al, 2009).…”
Section: Discussionsupporting
confidence: 93%
“…The latency and interval values observed in this study are in agreement with those obtained in dogs by other authors (Marshall, 1985;Knowles et al, 1988;Haagen et al, 1989;Harcourt et al, 2010) but shorter than those reported in human studies (Anias et al, 2004;Bento et al, 2009).…”
Section: Discussionsupporting
confidence: 93%
“…7,[12][13][14] Several authors have reported that BAEP responses in neonates and nursing infants are affected by the maturity of the auditory system. 7,12,[15][16][17][18][19] The effect of maturity is even more evident in premature infants; thus, the response pattern in these children differs from those in term neonates. 7,15,16,[19][20][21] Studies on the effects of neural maturity of the hearing system in premature neonates are sparse in the Brazilian literature.…”
Section: Introductionmentioning
confidence: 99%
“…9,17,18 The purpose of this study was to analyze the response pattern of premature and term neonates and nursing infants to the BAEP, considering the factors gender and ear, and to check the effect of auditory pathway maturity on the electrophysiological responses in a Brazilian population.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the electrophysiological records in the Integrity system were compatible with those of a The time of examination in movement is higher than at rest (p < 0.001), in both ears gold standard equipment available in the market, with respect to the average variable of the absolute latencies of the I, III, and V waves and the interpeak latencies I-III, III-V, and IV. According to the literature (24,25,26) the average values of the latencies of wave I range between 1.50 and 1.68 ms, those of wave III range between 3.50 and 3.80 ms, and those of wave V range between 5.50 and 5.64.…”
Section: Discussionmentioning
confidence: 97%